Aggregation Functions in Theory and in Practice - Torra, Vicenç; Mesiar, Radko; Baets, Bernard De.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book collects the abstracts of the contributions presented at AGOP 2017, the 9th International Summer School on Aggregation Operators. The conference took place in Skövde (Sweden) in June 2017. Contributions include works from theory and fundamentals of aggregation functions to their use in applications. Aggregation functions are usually defined as those functions that are monotonic and that satisfy the unanimity condition. In particular settings these conditions are relaxed. Aggregation functions are used for data fusion and decision making. Examples of these functions include means, t-norms and t-conorms, copulas and fuzzy integrals (e.g., the Choquet and Sugeno integrals).
The role of aggregation functions on auctions -- Aggregation of multidimensional data: a review -- k-maxitivity of order-preserving Homomorphisms of lattices -- Directional and Ordered Directional Monotonicity of Mixture Functions -- On Stability of Families for Improper Aggregation Operators -- On Implication Operators -- Some results about fuzzy consequence operators and fuzzy preorders using conjunctors.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence